A rapid construction strategy of NaYF4:Yb, Er@CDs nanocomposites for dual-mode anti-counterfeiting. Issue 11 (23rd May 2022) - Wei, Haopeng; Zheng, Yihao; Zhang, Xingcai; Liang, Ping; Xu, Xiaokai; Hu, Chaofan; Zhang, Xuejie; Lei, Bingfu; Liu, Yingliang; Zhuang, Jianle
Abstract : A rapid construction strategy is reported to achieve the composite structure of NaYF4 :Yb, Er and carbon dots (CDs) through electrostatic interactions. Abstract : A rapid construction strategy is for the first time developed to achieve the composite structure of NaYF4 :Yb, Er and carbon dots (CDs) through electrostatic interactions in only half a minute. The resulting NaYF4 :Yb, Er@CDs nanocomposites have superior dual-mode luminescence properties, showing promising application prospects in the field of advanced optical anti-counterfeiting.